Environmental Considerations for the Management of the Bivalve Fisheries of Bahía Magdalena (Mexico), a Coastal Lagoon at the Southern End of the California Current - Jiménez-Quiroz, María del Carmen; Barrón-Barraza, Francisco Javier; Cervantes-Duarte, Rafael; Funes-Rodríguez, René (Frontiers in Marine Science, 2021)
This study presents an overview of bivalve assemblages in Bahia Magdalena (BM, México) and the possible impact of environmental variability on these populations, constantly stressed by fishing. This lagoon is responsible for a high proportion of harvest of regional bivalves. First, we list the bivalve species reported in public biogeographic databases. Based on eight commercially exploited species, we described the composition of the bivalve assemblage and its biological characteristics, the history of fishery, and environmental variability in the marine area adjacent to the lagoon (1970–2019) and the habitat of bivalves (2002–2020). Sources of data were public databases and published literature. The enlisted species (n = 184) belong to six orders, and most are small and infaunal, but the structure of the assemblage is unknown. The fisheries began at different times and focused on the most valuable resources. Almost all harvest of bivalves had wide variations because of intensive fishing and a weak regulation frame. After 2015, the main resources were the Pacific wing-oyster (a new resource since 2017) and the geoduck clam due to the declining abundance of other resources (e.g., pen shells, Pacific calico scallop). There was a warming trend in the region since the 1970's, but the strongest El Niño-Southern Oscillation (ENSO) phases caused the most notable changes before 2013; after that year, a combination of large-scale phenomena increased the temperature significantly. The trend of chlorophyll-a abundance negatively correlated with temperature, but there was an almost constant supply of particulate organic matter in the interior of Bahia Magdalena (BM). After 2015, the quality of lagoon water gradually deteriorated, and in 2017 and 2019, harmful algal blooms developed, but the impact was not fully assessed. The challenges faced by the fishery are multiple (institutional weakness and regional warming); however, permanent monitoring programs of environmental conditions and critical biological variables should be implemented to design scenarios that allow fishery sustainability.